Goitre-Related Factors for Predicting Difficult Intubation in Patients Scheduled for Thyroidectomy in a Resource-Challenged Health Institution in North Central Nigeria - Olusomi, Bolaji Benjamin (Ethiop J Health Sci, 2018)
BACKGROUND: Airway management problems may arise when intubating patients with goitre scheduled for thyroidectomy. Goitres are not uncommon in sub-Saharan Africa, thyroidectomy being the main treatment. The aim of this study was to determine incidences of difficult intubation (DI), failed intubation (FI) and predictors of DI using a modified intubation difficulty score (IDS). METHODS: One hundred and twenty-five consenting patients with goitre scheduled for thyroidectomy were recruited. Goitre-related factors (GRF) of duration of illness, diagnosis, neck circumference, tracheal deviation and narrowing and retrosternal extension were recorded as well as Mallampati classification and BMI. At intubation, modified IDS was determined for each patient. Patients with modified IDS ≤ 5 were categorized as easy intubation group (E), and those with modified IDS >5 were categorized as difficult intubation group (D). The GRF of all patients in group D were compared with matched patients in group E. RESULTS: Incidence of DI was 13.6% with 2 (1.6%) cases of failed intubation. Comparing groups D and E, duration of illness was 4.28 ± 3.78 years in group D versus 7.44 ± 7.63 years group E, p = 0.1353. Neck circumference was 41.42 ±5.30 cm in group D versus 37.43±2.68 cm in group E, p = 0.0200. Tracheal deviation, narrowing and retrosternal extension, and surgical diagnosis were not significantly different among both groups. CONCLUSION: Incidence of DI was 13.6% and that of FI was 1.6%. Neck circumference was found to be a predictor of difficult intubation in goitre patients scheduled for thyroidectomy using the modified IDS.